Collective Curation across Difference: Performing Live with Race, Gender, and Sexuality - Ruiz, Sandra (Performance Matters, 2023)
This piece charts the creation of a gallery within an ethnic studies unit, a syllabus in conjunction with said space, and a student-artist group exhibition titled Objects Who Hold/Objects Who Let Go. The exhibition asks one to consider how we learn to withhold and let go of the memories that bridge gaps between permanence and ephemerality. Curated in community by the artists themselves, the show drives the audience to embrace this tension of holding on and letting go as one intentionally engages with experimental art that pushes the boundaries of race, gender, and sexuality across expressions of loss and mourning.